Segregation-controlled self-assembly of silver nanowire networks using a template-free solution-based process. Issue 18 (28th April 2021) - Shin, Ji Won; Lim, Hyo-Ryoung; Cho, Hong-Baek; Kwon, Young-Tae; Choa, Yong-Ho
Abstract : Metal conductive patterning has been studied as an alternative to the most commonly used indium tin oxide electrodes. Abstract : Metal conductive patterning has been studied as an alternative to the most commonly used indium tin oxide electrodes. Printed electrodes are fabricated by several complicated processes including etching, photolithography, and laser- and template-based techniques. However, these patterning methods have increasingly encountered critical issues of long manufacturing times and high equipment costs that necessitate vacuum and high-temperature conditions. In this study, we present a template-free solution-based patterning method for the fabrication of transparent electronics by inducing segregation-based networks of silver nanowires (SGAgNWs); this is a potential method to fabricate cost effective and scalable optoelectronics. Micro-dimensional fine-patterned segregated networks with conductive cells are created by the self-assembly of one-dimensional nanomaterials under optimal ink conditions wherein different types of solvents and aspect ratios of silver nanowires (AgNWs) are formulated. Photoelectric properties can be controlled by adjusting the size of the cell, which is an empty domain surrounded by the AgNW assembly with microscale cell-to-cell distance dimensions ranging between 4 to 345 μm. The as-obtained AgNW metal grid—formulated on a polyethylene terephthalate film—was identified as a high-performance transparent electrode (TE) device with excellent optoelectronic properties of 87.08% transmittance and 50 Ω □ −1 resistance. In addition, the electrical conductivity of the TE film is enhanced with a very low haze of less than 4% because of the intense pulsed light treatment that diminished the sheet resistance to 21.36 Ω □ −1, which is attributed to the creation of welded silver networks. The SGAgNW concept for TE technology demonstrates a very promising potential for use in next-generation flexible electronic devices.